The Keys of the Historical and Artistic Context of Compostela in the Turn of the Century (19th-20th) through Industrial Arts: the Case of the Silversmith - Pérez Varela, Ana (Madrygal. Revista de Estudios Gallegos, 2021)
This paper explores five elements that we chose as representative items in the artistic scene of Santiago de Compostela between the nineteenth and the twentieth century, when the favourable historical and economical context motivated certain changes that distinguish this art from the past nineteenth century art. Revisiting the second inventio of the Apostle, the institutionalization of the education of the guilds, the neo-medieval historicism style, and the construction of nationalist identity, we pretend to explore the relationship between these factors and the industrial arts –our subject of study– and in which way these arts are a clear reflection of their artistic and aesthetic context.